Penatalaksanaan early childhood caries Management of early childhood caries - Fajriani Fajriani; Hendrastuty Handayani (DiscoverSys Inc., 2011)
Early childhood caries (ECC), also known as milk bottle caries is a syndrome of severe tooth decay, occurs ininfants and children, is an infectious disease that develops rapidly and lead to health problems in children. Thissyndrome can be caused by inappropriate use of bottles. Most cases of untreated ECC to children aged 20 months.At this stage many children need serious treatment, because this will result in trauma to both the children andparents. The most common treatment ECC and other dental diseases have been included in each treatment ofdisease. Efforts to educate families about dental hygiene and practice start a diet, the high rate of recurrence of anyevidence of disease ranging from tooth decay to the failure of the treatment plan resulted in the need for specialattention to this disease. This paper is expected to be a good input for a dentist in the treatment of ECC